Development of a Community-Based Spiritual Life Review Program for Promoting Resilience of Elders Residing in Disaster-Prone Areas - Satria, Budi; Isaramalai, Sang-arun; Komjakraphan, Patcharee (Nurse Media Journal of Nursing, 2012)
Background: Nowadays disasters are a common occurrence in the world. The elderly are in a vulnerable condition in terms of disasters and need help to recover from the hardship caused if they are caught in such a disaster. Two significant contributors to elderly people having sufficient resilience to be able to deal with such disasters are spiritual support and social support. Purpose: To develop a program specifically for Muslim elderly in Indonesia for promoting resilience. Method: The processes of developing the program were conducted in 2011, and included a critical review of the literature, constructing the elements of the actual program, validating the contents of the program by three experts, revising the program according to the experts‟ suggestions, and finally pilot-tested the final version of the program on a group 12 elders in Banda Aceh, Indonesia. Result: The program protocol established in this program includes five stages: (1) reviewing individual spiritual life experiences using memorable photos; (2) appreciating feelings among group members (3) re-evaluating the participant‟s life by looking to the group‟s album, (4) reconstructing the participants‟ life, and (5) affirming the six spiritual dimensions of the Islamic religion by the religious leader. Keywords: Community-based, spiritual, life review, resilience, elderly, adversity.